Qualitative Study of Supporting Factors for Integrated Health Post Cadre Participation in Promotion of Local Natural Substance as Appetite Enhancer Supplement - Abdurrahman Ali, Nur Aini; Yuniastuti, Ari; Handayani, Kasmini (Public Health Perspective Journal, 2021)
The problem of malnutrition and severe malnutrition among toddlers in Bima regency remains very high. Thus Cadres Integrated Health Post (Posyandu) participated in promotion of local natural substances as an appetite enhancer supplement to prevent malnutrition efforts of toddlers. The purpose of this research was to qualitatively analyze the factors supporting the participation of Integrated Health Post (Posyandu) cadres in promoting substances as an appetite enhancer supplement. The study employed a qualitative approach with a phenomenological design. The focus of the study was to know in depth about the supporting factors for the participation of Integrated Health Post (Posyandu) cadres in promoting local natural substances as an appetite enhancer supplement. The determination of information using purposive and snowball techniques. Data collection techniques by means of interviews, observation and documentation. The data validity technique used source triangulation, technique triangulation, time triangulation. The data analysis technique uses miles and huberman models. The results showed that the supporting factors for the participation of Integrated Health Post cadres in promoting substances as an appetite enhancer supplement consisted of 1) Predisposing factors : knowledge of cadres about local natural substances as an appetite enhancer supplement and basic knowledge of plant, positive attitudes, culture (traditions and beliefs); 2) Enabling factor: availability of local natural materials; 3) Reinforcing Factors: Educate Women on Various Aspects of Family Welfare (PKK) activator team and public health center officers (Puskesmas).